Penyalahgunaan izin tinggal WNA di Bali: Apakah berelasi dengan mass tourism? - Korassa Sonbai, Angelique Camelita; Resen, Putu Titah Kawitri (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The presence of foreign tourists in Bali will certainly influence immigration regulations and policies. The variety of destinations in Bali means that foreign tourists also use different visas. They use different types of visas to ensure there are no residency violations, according to the immigration authority that regulates the regulations. As part of law enforcement, Bali certainly has regional regulations regarding visits by foreign tourists. Immigration is a regulatory area, and tourism information managers play an important role in enforcing immigration regulations. Tourism is a group trip whose aim is to have fun, increase knowledge, and carry out other activities. The Bali government's efforts to develop Indonesia's tourism potential to increase the number of tourists visiting Bali next year include accelerating the completion of several accessibility infrastructure projects, encouraging the development of tourist destinations, and strengthening tourism promotion. Tourists who visit Bali have their own interests. Conditions for tourists visiting Bali, especially conditions for visits by foreign tourists, can be differentiated based on the visa used. For legal reasons and in accordance with applicable regulations, such as visits due to government, socio-cultural, commercial, or professional duties, the presence of foreign nationals is legal if it occurs through registered channels such as ports, airports, or other areas designated by the Ministry of Law and Human Rights. The Bali Province Immigration implemented by the Immigration includes taking action against Indonesian citizens (WNI) of the Bali Province and foreign citizens of the Bali Province. Criminal prosecution will be implemented in accordance with applicable laws and regulations. This is to discourage immigration violators, especially in Bali Province. Apart from its deterrent impact, it also has other legal objectives, namely protecting social interests and regulating social order. Law enforcement that approaches the law as everyday law is then tested and applied in the world of everyday reality. This refers to the sociology of law, which studies law as a social phenomenon as well as the relationship between other social phenomena. Legal sociology tries to explain legal practices such as legislation, adjudication, and others. Legal sociology tries to explain why this practice occurs, what causes influence it, the background, and others too. In enforcing the Immigration Violations Law, Bali Province immigration officers face obstacles, namely internal and external borders. Immigration law enforcement has either internal or external borders.